(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article examines the opinions of foreign and domestic scientists on the introduction of a modern system of human resources management. Also, the essence of the stages of evolutionary approaches to human resources management, the tasks of introducing a modern management system and ways to solve them are highlighted.